The importance of educating student teachers in inclusive education. A disability perspective. (Kairaranga, 2008)
In schools today inclusion involves a challenge to attitudes and expectations within educational communities.The New Zealand Disability Strategy (Minister for Disability Issues, 2001), is a guide for government action to promote a more inclusive society. Out of its 15 Objectives, Objective 1encourages and educates the community and society to understand, respect and support disabled people. Objective 3 looks at providing the best education for disabled people.Objective 5 fosters leadership by disabled people. The summary states that New Zealand will be fully inclusive when it's a society that highly values our lives and continually enhances our full panicipation.Educators must be committed to The New Zealand Disability Strategy because its main locus is about a fully inclusive community. Often, through role models, strong messages challenge negative assumptions and prove that there are alternative ways of looking at the world. Generally, those who are the most critical to implementing inclusion, such as teachers, are introduced to the notion by individuals for whom it is a theoretical, rather than a lived concept.This article involves a sharing of experiences of two women who are involved in teaching inclusion at tertiary level, who live with physical disabilities and who have proved this to be a powerful combination in changing attitudes.